(untitled) (Ameghiniana, 2013)
In recent years the phytolithological tenninology has been unified. Several English terms have not a precise Spanish translation, because they have more than one meaning and/or a wrong ethymology. In order to fill this gap a correlation between English-Spanish tenns is here proposed. A bibliographic recapitulation is also presented.